The Multidimensional Nature of Quest Motivation - Beck, Richard Allan 1967-; Jessup, Ryan K. (2004)
Although Daniel Batson's (1976) construct of “Religion as Quest” has been widely applauded as an important theoretical innovation in the assessment of religious motivation, there are lingering concerns regarding the validity of the Quest construct. This study follows up some past suggestions in the literature that Quest may be a multidimensional construct and that facets of Quest may have very different relationships with religious variables. To test these hypotheses we constructed a multidimensional measure of Quest and administered it to 183 college students along with measures of spiritual well-being, Christian orthodoxy, extrinsic and intrinsic religiosity, and Batson's 12-item Quest measure. Overall, the results suggest that Quest is indeed a multidimensional construct and that the dimensions of Quest need to be assessed separately to assess Quest's construct validity. Specifically, two broad trends were noted. First, some facets of Quest seem to capture the free-roaming existential Quest Batson has frequently described. However, other facets of Quest seem to be compatible with orthodox Christian beliefs, suggesting that possessing metaphysical convictions are compatible with Quest-like attributes.